(untitled) (Research, Society and Development, 2022)
The present study is a bibliographic research with the objective of analyzing the incidence of anxious and depressive symptoms in medical students and the factors associated with their development, through the review of 20 scientific articles available in the bireme and scielo databases, using the descriptors “depression”, “anxiety” and “medical students”, published from January 2012 to June 2022. The analysis performed based on the studied literature showed a higher incidence of depressive and anxious symptoms among medical students, compared to with the general public. There were several risk factors associated with this prevalence, such as female gender, parental distance, distance between home and educational institution, less availability for leisure and hours of sleep, abuse of licit and illicit substances, self-demand and dissatisfaction with the course. Therefore, it is necessary to promote policies to encourage the care of students’ mental health, encouraging the search for professional help and the alert regarding the symptoms that involve being or not having Depression or Anxiety, aiming at prevention and monitoring.